All in the family: Economies of scale in retail and institutional investment management - CHOI, Darwin (Institutional Knowledge at Singapore Management University, 2016)
This paper examines the (dis)economies of scale related to the joint management of retail mutual funds and institutional funds (i.e., investment portfolios catering to institutional clients). Similar to well-known observations for mutual funds, the performance of institutional funds is negatively related to fund size but positively related to fund family size, suggesting diseconomies of scale at individual fund level and economies of scale at fund family level. More importantly, there is spillover of the family size effect -- the performance of mutual funds (institutional funds) is positively related to the total institutional assets (mutual fund assets) managed by the same firms. We also find that certain types of funds -- e.g., larger mutual funds and institutional funds with higher fees -- benefit more from this spillover effect, suggesting that large investment firms are able to deploy firm-wide resources to favor a subset of funds that are of high value to the firms. However, there is no evidence that jointly managed funds, either retail or institutional, perform worse than independently managed ones. Overall, our findings suggest that the prevalence of jointly managed retail and institutional funds is consistent with economies of scale in the investment management industry.